Disminore dan gangguan aktivitas praktikum di laboratorium kebidanan - Indraswari Siscadarsih; Nur Indah Kusuma Dewi (Poltekkes Kemenkes Yogyakarta, 2024)
Menstrual problems pose many physical, socio-cultural and economic challenges that may hinder life activities, especially the ability to go to school, college, practicum or participate in physical activities. The role of laboratories is very important in the development of science which is growing rapidly in universities today. This research revealed that 9 out of 10 respondents with severe dysmenorrhea had their practical activities disrupted. Health vocational students in Indonesia are required to attend 100% of practicums with a composition of 60% practice during lectures. Students must make up practical work hours when they are absent for any reason. This condition of course makes the practicum ineffective and even increases the risk of work accidents. The aim of this research is to determine whether there is a relationship between dysmenorrhea and disruption of practical activities in the laboratory. This research is a descriptive study with a quantitative approach using a cross-sectional design by measuring activity disorders and the severity of dysmenorrhea as assessed using VMSS. The sampling technique in this research used purposive sampling with a total sample of 311 students. The inclusion criteria were being unmarried, having menstruated for at least 1-2 years and experiencing primary dysmenorrhea. This research was conducted at the Yogyakarta Ministry of Health Health Polytechnic Midwifery Laboratory in October 2022. The data analysis used was the Fisher exact test with a p value of 0.001 and OR 4.2. This shows that there is a significant relationship between dysmenorrhea and disruption of practical activities in the laboratory.